2013
DOI: 10.1016/j.indcrop.2012.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Biochar production from waste rubber-wood-sawdust and its potential use in C sequestration: Chemical and physical characterization

Abstract: Biochars have received increasing attention because of their potential environmental applications such as soil amending and atmospheric C sequestration. In this study, biochar was produced from waste rubber-wood-sawdust. The produced biochars were characterized by Brunauer-Emmett-Teller (BET) gas porosimetry, scanning electron microscopy (SEM), X-ray diffraction (XRD), thermogravimetric analysis (TGA), and Fourier transform infrared spectroscopy (FTIR). Pyrolysis temperature was shown to have a strong influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
113
1
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 325 publications
(135 citation statements)
references
References 24 publications
10
113
1
11
Order By: Relevance
“…A band at 1584 cm -1 was attributed to aromatic material, and a shoulder at 1154 cm -1 was associated with the structures of cellulose and hemicellulose carbohydrates. Ghani et al 25 characterized biochar produced from rubber wood waste and reported that the IR spectra showed the formation of aromatic products with lower hydrogen contents, compared to the original material. In the present work, AB was obtained using a pyrolysis temperature of 600 °C, while MB was produced at 400 °C, so AB was more liable to changes in chemical composition due to carbonization, relative to the EH parent material.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A band at 1584 cm -1 was attributed to aromatic material, and a shoulder at 1154 cm -1 was associated with the structures of cellulose and hemicellulose carbohydrates. Ghani et al 25 characterized biochar produced from rubber wood waste and reported that the IR spectra showed the formation of aromatic products with lower hydrogen contents, compared to the original material. In the present work, AB was obtained using a pyrolysis temperature of 600 °C, while MB was produced at 400 °C, so AB was more liable to changes in chemical composition due to carbonization, relative to the EH parent material.…”
Section: Resultsmentioning
confidence: 99%
“…Hemicellulose pyrolysis products include non-condensable gases (CO, CO 2 , H 2 , and CH 4 ), low molecular weight compounds (carboxylic acids, aldehydes, alkanes, and ethers), and water. 25 An intense decomposition peak in the region 200-400 °C was observed for the TAN precursor material used to produce MB, which could be attributed to the decomposition of polyphenolic compounds. The production of MB using a pyrolysis temperature of 400 °C would therefore lead to decomposition of these compounds.…”
Section: Thermogravimetric Analysis (Tga)mentioning
confidence: 98%
See 2 more Smart Citations
“…They found by BET and FTIR that an increase in process temperatures results in higher surface area, more development of aromatic compounds and a decrease in aliphatic groups. Ghani et al [10] evaluated the properties of biochar from waste rubber-wood-sawdust by pyrolysis between 450 °C and 850 °C, founding by BET analysis that the total surface is lower than 10 m 2 /g for lower temperatures and around 200 m 2 /g for higher temperatures. Kim et al [11] evaluated the properties of biochar from pitch pine produced by fast pyrolysis at different temperatures (300-500 °C); they obtained BET surface areas between 3.0 and 175 m 2 /g that increased with the pyrolysis temperature; from the FTIR spectra, they found that the O-H stretch peak (3600-3200 cm -1 ) decreases in the spectra for biochar.…”
Section: Introductionmentioning
confidence: 99%